The Relationship Between Machiavellian, Personality Traits, and Organizational Ethical Culture and Auditor Dysfunctional Behavior (A Survey of Auditors at the Audit Board of the Republic of Indonesia (BPK RI)) - Dhahlia Dian Wijaya Wardhani; Poppy Sofia Koeswayo; Ahmad Zakie Mubarok (Dinasti Publisher, 2025)
This research was conducted based on the phenomenon of dysfunctional auditor behavior, which is a major concern that has the potential to undermine the reputation of the Audit Board of the Republic of Indonesia (BPK) and one of the challenges for the BPK in preparing auditors who are able to apply the organization's core values in carrying out audit duties. The purpose of this study is to determine the influence of machiavellian, personality traits, and organizational ethical culture on dysfunctional auditor behavior. The purpose of this study is to determine the influence of machiavellian, personality traits, and organizational ethical culture on dysfunctional auditor behavior. This research method is a quantitative method with a survey approach on auditors at the BPK RI. This study uses primary data obtained through online questionnaires by 268 respondents who are sampled in the study. The data analysis method of this study is descriptive statistics and path analysis using the IBM SPSS Statistics 26 program. The results show that Machiavellian have a significant positive effect on dysfunctional auditor behavior, while personality traits have a significant negative effect on dysfunctional auditor behavior. Meanwhile, organizational ethical culture has a negative but insignificant effect on dysfunctional auditor behavior.